Enhancing the Students Writing Ability by Using Comic Strips - Humola, Yusda; Talib, Rasuna (Sebelas Maret University, 2016)
This article reports on the results of a study aiming to investigate whether the comic strips can help students to enhance their writing skill in English. This study was conducted at the tenth class of SMA Negeri I Tapa 2014/2015 in academic years with 25 students as the participants. The text in focus was narrative. The study used an action research by using Kemmis and Taggartâ s design that consists of four steps, namely planning, acting, observing, and reflecting. The data were collected from observation and written test. The data of observation were obtained the teacher and studentsâ activities in teaching learning writing. Whereas, the data of written test were obtained from the studentsâ writing task in every cycle. Some aspects used to analyze the students writing ability, namely content, organization, vocabulary, language use and mechanics ones. The results indicates that despite some aspects that still need improvement, the use of comic strips can enhance students writing skill in narrative text. The portraits of studentsâ progress in writing English narrative text of some cycles show that in the first cycle, only four of twenty five students (16%) who can write narrative texts as the successful indicator 80%. In the second cycle, ten students (40%) were success, then in the third cycle, twenty two students (88%) could reach the value 80 or more as the criteria of successful. Observation data shows that the students were motivated to write English narrative text by using comic strips both in group and individual works. Whereas, the commitment of English teacher as a model and colleagues to reflect and to renovate the teaching and learning process was running well on each cycle. Based on the results of the study, it is recommended that comic strips be implemented in other genres, notably recount text or other language skills, and other countries.